(3MOjK eMeO Hf jhSa GdQbis - (3eMeO Hf jhSa GdQbjs
(3ChdgG (B:s
(3CNHQfG GdTjN CHh GdTjN GHQGgje Hf CHj WGgQ HQcGJ Yf GfS Hf eGdc bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B:( (3Efi jhe GdbjGeI HGH GdLfI aGSJaJM ajbhd GdNGRf ef CfJ aCbhd eMeO ajbhd bO GeQJ Cf dG CaJM dCMO bHdc (B) s
(3BNQgG (B:s
(3SeYJ LYaQ GdMdHi jbhd SeYJ GdLfjO jbhd SeYJ SjOi jbhd eG CMH Cf CehJ ai HdO CNGa Gf dG jbHdfi GdGQV BNQ GdLRA hGdMeO ddg QH GdGdejf s
(3HBNQgG SeGYGJ cKjQIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdCMeOjI (B_ (3JhfS (B(5032(8)) s
Keywords: (3GdMOjK h GdeUWdMs